Differentially expressed genes in the caecal and colonic mucosa of Landrace finishing pigs with high and low food conversion ratios. Issue 1 (December 2017) - Tan, Zhen; Wang, Yuan; Yang, Ting; Xing, Kai; Ao, Hong; Chen, Shaokang; Zhang, Fengxia; Zhao, Xitong; Liu, Jianfeng; Wang, Chuduan
Abstract The feed conversion ratio (FCR) is an essential economic trait for pig production, and is directly related to feed efficiency. Studies identifying the differential expression of functional genes involved in biological and molecular mechanisms in the intestine in relation to growth performance are rare. In this study, RNA-Seq was used to identify transcriptomes in caecal and colonic mucosal tissues in order to determine the differential expression of genes from two full-sibling pairs and two half-sibling pairs of Landrace finishing pigs with opposing FCR phenotypes. In total, 138 (comparison of high and low FCR in caecal mucosa), 64 (comparison of high and low FCR in colonic mucosa), and 165 (contrast between the caecal and colonic mucosa) differentially expressed genes were identified. Some of these genes were functionally related to energy and lipid metabolism, particularly short chain fatty acids metabolism, as well as gastrointestinal peristalsis and ion transport. Functional annotation were performed to identify differentially expressed genes, such as GUCA2A, GUCA2B, HSP70.2, NOS2, PCK1, SLCs, and CYPs, which may positively influence feed efficiency in Landrace pigs. These differentially expressed genes need to be further tested for candidate genes that are related to feed efficiency.